ANALISIS PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (STUDI DI DESA SUBUR KECAMATAN AIR JOMAN KABUPATEN ASAHAN) - Miftahul Husna; Zaid Afif; Komis Simanjuntak (JURNAL PIONIR, 2022)
The village is an area where the community lives in a cooperative manner, with the same customs, norms and procedures in regulating community life. The purpose of this study was to determine the management of the Village Income and Expenditure Budget and the obstacles in managing the Village Income and Expenditure Budget. The process of managing the Village Revenue and Expenditure Budget starts from planning, implementation, administration, reporting and accountability. The formulation of the problems raised in this paper are: 1) Is the management of the Village Income and Expenditure Budget for the Village of Subur Village, Air Joman District, Asahan Regency in accordance with the Laws and Regulations. 2) What are the obstacles faced in the process of managing the Village Income and Expenditure Budget in Subur Village, Air Joman District, Asahan Regency. This study uses a legal research method with an empirical approach, namely the approach used by researchers to describe the conditions seen in the field as they are. Based on the research results from the title above, it can be seen that in general, the management of the Village Income and Expenditure Budget in Subur Village is well managed in accordance with the principles of regional financial management.  Keywords: Management, APBDesa, Budget